Measurement of four-jet differential cross sections in root s=8 TeV proton-proton collisions using the ATLAS detector - Onofre, A. (2015)
Differential cross sections for the production of at least four jets have been measured in proton-proton collisions at root s = 8 TeV at the Large Hadron Collider using the ATLAS detector. Events are selected if the four anti-k(t) R = 0.4 jets with the largest transverse momentum (p(T)) within the rapidity range vertical bar y vertical bar < 2 : 8 are well separated (Delta R-4j(min) > 0.65), all have p(T) > 64 GeV, and include at least one jet with p(T) > 100 GeV. The dataset corresponds to an integrated luminosity of 20.3 fb(-1). The cross sections, corrected for detector effects, are compared to leading-order and next-to-leading-order calculations as a function of the jet momenta, invariant masses, minimum and maximum opening angles and other kinematic variables.